Development of dense Hydroxyapatite from natural and synthetic sources - Sri Asliza, Amin; S. A., Abu Bakar; Azlin Fazlina, Osman; Syed Nuzul Fadzli, Syed Adam; Norsuria, Mahmed; Mohd Zaheruddin, Kasmuin (University Malaysia Perlis (UniMAP), 2011)
Jointly organized by School of Environmental Engineering, School of Materials Engineering, and School of Bioprocess Engineering, Universiti Malaysia Perlis (UniMAP), 9th - 11th June 2007 at Park Royal Hotel, Penang, Malaysia.